Modeling Lay People’s Ethical Attitudes to Organ Donation: A Q-Methodology Study - Hammami MM; Hammami MB; Aboushaar R (Patient Preference and Adherence, 2020)
Muhammad M Hammami, 1, 2 Muhammad B Hammami, 3 Reem Aboushaar 4 1Clinical Studies and Empirical Ethics Department, King Faisal Specialist Hospital and Research Centre, Riyadh, Saudi Arabia; 2Alfaisal University College of Medicine, Riyadh, Saudi Arabia; 3Division of Gastroenterology, Department of Medicine, John Hopkins University, Baltimore, MD, USA; 4MS IV, Florida Atlantic University, Boca Raton, FL, USACorrespondence: Muhammad M HammamiClinical Studies and Empirical Ethics Department, King Faisal Specialist Hospital and Research Centre, P O Box # 3354 (MBC 03), Riyadh 11211, Saudi ArabiaTel +966-11-442-4527Fax +966-11-442-7894Email Muhammad@kfshrc.edu.saBackground: Organ donation is commonly evaluated by biomedical ethicists based largely on principlism with autonomy at the top of the “moral mountain.” Lay people may differ in the way they invoke and balance the various ethical interests. We explored lay people’s ethical attitudes to organ donation.Methods: Respondents (n=196) ranked 42 opinion-statements on organ donation according to a 9-category symmetrical distribution. Statements’ scores were analyzed by averaging-analysis and Q-methodology.Results: Respondents’ mean (SD) age was 34.5 (10.6) years, 53% were women, 69% Muslims (30% Christians), 29% Saudis (26% Filipinos), and 38% healthcare-related. The most-agreeable statements were “Acceptable if benefit to recipient large,” “Explicit donor consent and family approval for live donation,” “Acceptable if directed to family member,” and “Explicit donor consent and family approval for postmortem donation.” The most-disagreeable statements were “Donor consent and family approval not required for postmortem donation,” “Acceptable with purely materialistic motivation,” and “Only donor no-known objection for postmortem donation.” Women, Christians, and healthcare respondents gave higher rank to “Explicit donor consent and family approval for live donation,” “Only donor family consent required for postmortem donation,” and “Acceptable if organ distribution equitable,” respectively, and Muslims gave more weight to donor/family harm (p ≤ 0.001). Q-methodology identified various ethical resolution models that were associated with religious affiliation and included relatively “motives-concerned,” “family-benefit-concerned,” “familism-oriented,” and “religious or non-religious altruism-concerned” models. Of 23 neutral statements on averaging-analysis, 48% and 65% received extreme ranks in ≥ 1 women and men Q-methodology models, respectively.Conclusion: 1) On average, recipient benefit, requirement of both explicit donor consent and family approval, donor-recipient relationship, and motives were predominant considerations; 2) ranking of some statements was associated with respondents’ demographics; 3) Q-methodology identified various ethical resolution models that were partially masked by averaging-analysis; and 4) strong virtue and familism approaches in our respondents provide some empirical evidence against principlism adequacy.Keywords: organ donation, familism, virtue, ethics of care, principlism, Q-methodology